2019
DOI: 10.1073/pnas.1903698116
|View full text |Cite
|
Sign up to set email alerts
|

Precision mapping of snail habitat provides a powerful indicator of human schistosomiasis transmission

Abstract: Recently, the World Health Organization recognized that efforts to interrupt schistosomiasis transmission through mass drug administration have been ineffective in some regions; one of their new recommended strategies for global schistosomiasis control emphasizes targeting the freshwater snails that transmit schistosome parasites. We sought to identify robust indicators that would enable precision targeting of these snails. At the site of the world’s largest recorded schistosomiasis epidemic—the Lower Senegal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(125 citation statements)
references
References 64 publications
5
118
0
2
Order By: Relevance
“…S2) suggest it might be possible to use geospatial models to predict seroprevalence over larger areas with less densely measured communities, but it remains an open question. It might also be possible to improve geostatistical model predictions by extending models to include more geospatial layers (17) or by including more refined measures of snail habitat derived from remotely sensed images, such as those recently proposed in Senegal (38). The force of infection analyses assumed no seroreversion over the age range (change from seropositive to seronegative), and longitudinal studies of children following infection and successful treatment without reinfection would be useful to confirm postinfection SEA IgG kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…S2) suggest it might be possible to use geospatial models to predict seroprevalence over larger areas with less densely measured communities, but it remains an open question. It might also be possible to improve geostatistical model predictions by extending models to include more geospatial layers (17) or by including more refined measures of snail habitat derived from remotely sensed images, such as those recently proposed in Senegal (38). The force of infection analyses assumed no seroreversion over the age range (change from seropositive to seronegative), and longitudinal studies of children following infection and successful treatment without reinfection would be useful to confirm postinfection SEA IgG kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy of field identifications were verified by molecular barcoding technique: at the time of shedding or dissection, in all fork-tailed cercariae liberated from snails were placed individually on WhatmanFTA © cards and sequenced to distinguish human-infective Schistosoma haematobium and S. haematobium–bovis hybrids from S. bovis (schistosome parasite of cattle) and other non-human furcocercous (forktailed) trematode species [8]. The identification of the parasites was based on multi-locus analyses with one mitochondrial ( cox 1) and two nuclear ( ITS 1+2 and 18S) genes [9]. Cercariae on FTA cards were accessioned into the Schistosomiasis Collection at the Natural History Museum (SCAN) [10].…”
Section: Methodsmentioning
confidence: 99%
“…PCR and sequencing conditions were chosen as previously published [12]. Sequencing was performed on an Applied Biosystems 3730XL analyser (Life Technologies, UK) [9]. The field ID guidelines for morphologies of snails and parasites are provided in the supplemental materials (see S2 Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…Although the failure of PZQ to eliminate schistosomiasis is disappointing, it is not especially surprising; for organisms with complex life cycles, population consequences of mortality of a single life history stage may be complicated by density dependence in intervening life history stages (28). Indeed, a recent study suggested that infection risk for humans is controlled by the availability of intermediate snail hosts (29). Furthermore, life-history tradeoffs could allow schistosomes to compensate for PZQ-induced death, either within or between life history stages (30).…”
Section: Introductionmentioning
confidence: 99%